Northwest History. Aviation 8. Chamber of Commerce, United States. (1937)
Alaskans Want Wild Life Reserve. ALASKANS WANT WILD LIFE RESERVE ANCHORAGE, Alaska, Feb. 3. (/P)—Setting aside of Lake George, Alaska's famous self-emptying lake, as a game preserve was sought today by the Anchorage Chamber of Commerce. The chamber asked the federal biological survey to create the preserve to protect bears, goats, sheep and moose pending development of the area as a tourist attraction. A glacier, which dams the lake annually, melts every August, emptying the lake into Cook inlet, south of here. When the lake is full it is 29 miles long, but after the glacier releases its waters, the lake is only a half mile long.